Criação de spin-offs à luz da teoria dos custos de transação: uma investigação em universidades e institutos de pesquisa da região sudeste do Brasil - Soares, Thiago José Cysneiros Cavalcanti (Universidade Federal de São Carlos, 2015)
Spin-off companies can be defined as firms founded to exploit intellectual property or specific capabilities developed at universities and research institutes. In this context, the main goal of this work was to understand from the perspective of Transaction Costs Theory which are the main factors responsible for the creation of such companies in universities and research institutes of southeastern Brazil. In order to do so, a survey was conducted with the Technology Transfer Offices directors of 102 universities and research institutes of this region. Through a literature review in academic entrepreneurship, creation of spin-offs, Transaction Costs Theory and Brazilian innovation system it was possible to develop a theoretical and conceptual model for the creation of spin-off companies. This model indicates that the likelihood of spin-offs creation increases with: (1) low information seeking costs; (2) low bargaining costs; (3) high degree of interaction between researchers and technology transfer offices; and (4) policies aimed to the reduction of transaction costs within the creation process of these companies. The results were investigated through a descriptive analysis and using two separate regression techniques. The first technique used was a logistic regression, which related the (non) existence of spin-offs to the independent variables proposed by the theoretical and conceptual model. The second technique, in turn, was a linear regression using as dependent variable the number of spin-off companies at the investigated institutions per thousand researchers. The data analysis indicated there were signs that lower information seeking costs, high degree of interaction between researchers and technology transfer offices, as well as the existence of policies aimed to reduce transaction costs in the spin-off creation process are favorable for the generation of these companies. Though, there was no evidence that suggest bargaining costs influence the likelihood of the creation of spin-offs at universities and research institutes.
Keywords: Empresas; Spin-offs acadêmicos; Custos de transação; Transferência de tecnologia; Empreendedorismo; Sistema de inovação; Spin-offs; Transaction costs; Technology transfer; Academic entrepreneurship; Brazilian innovation system; ENGENHARIAS::ENGENHARIA DE PRODUCAO